Investigation of the dynamic on-state resistance of AlGaN/GaN HEMTs. Issue 9 (August 2015) - Rzin, M.; Labat, N.; Malbert, N.; Curutchet, A.; Brunel, L.; Lambert, B.
Abstract: The dynamic on-state resistance ( RON ) increase in AlGaN/GaN high-electron-mobility transistors (HEMTs) has been investigated by pulsed I–V measurements on devices issued from UMS GaN technology. We have studied the influence of the measurement setup on the pulsed I–V measurements and highlighted the importance of the IDS ( t ) waveforms to verify the validity of the measurements. The RON is not sensitive to short time transients below 10 μs as well as for fresh and HTRB aged devices. The dynamic resistance ( RON ) is doubled in off-state conditions by increasing VDS0 from 0 V to 50 V. The threshold voltage VTH of aged devices has not shifted during the HTRB aging test carried out for 2200 h. Therefore, trapping effects responsible for the increase of RON are rather more located in the gate-source and drain–source access regions than under the gate.